Asociación entre la Cirugía Lasik y la Disfunción de Glándulas de Meibomio (2023)
The meibomian glands are essential palpebral cellular structures in the consistency and balance of the tear film, which contribute to the health and stability of the ocular surface; the glandular structure of the eyelid epithelium provides lipids (meibum) that guarantee stability and lipid supply in the tear film (PL), through a complex physiological process that includes hormonal stimulation, neurosensory and mechanical, where blinking and the stability of the epithelia corneal and intact conjunctiva, fulfill an essential function.